Investigating Kalmykia’s History during the Russian Civil and Great Patriotic Wars: the Impact of P. E. Alekseeva - U. Ochirov (Монголоведение, 2019)
The article celebrates the 95th anniversary of Praskovia E. Alekseeva, a major bibliographer of the Kalmyk Scientific Center of the RAS and the oldest worker of Kalmykia’s science and culture institutions. The paper analyzes her impact – widely accepted as essentially significant and even crucial — on studies of Kalmykia’s history during the Russian Civil and Grate Patriotic Wars. It is the author’s opinion that the most precious work here is that dealing with annotated lists of participants of the Great Patriotic War (referred to different categories) conscripted from the former Kalmyk District of Rostov Oblast, and lists of soldiers of the 110th Kalmyk Cavalry Division. The project was extremely difficult and required long years of meticulous work, but P. E. Alekseeva did manage to solve the assigned tasks.